Mama in vzgojiteljica kot ocenjevalki otrokove govorne kompetentnosti - Fekonja Peklaj, Urška (Psihološka obzorja (Ljubljana), 2008)
Many researchers include child's parents as assessors of his/her language development as the results of many studies suggest their assessments to be valid and reliable measures of child's language competence. In their longitudinal study, presented in this paper, we examined whether child's mother and his/her preschool teacher can provide a valid estimation of child' language development. The sample included 80 Slovenian children from different preschool institutions, aged 3;1 years at first and 4;1 years at second assessment. Children's language competence was assessed individually, directly by the testators using Language development scale and Storytelling test and indirectly by mothers and preschool teachers using the Child's language competence questionnaire for parents and preschool teachers. The achieved results showed that the estimates given by mothers and preschool teachers represent valid measures of child's language competence but not stable in time. The estimations given by mothers and preschool teachers explain a small share in variability of children's achievements on the Language development scale and Storytelling test
Keywords: govorni razvoj; govor; ocenjevanje; matere; vzgojiteljice